Diagnosis and Management of Ischemic Mitral Regurgitation: Evidence-Based Clinical Decision Making at the Point of Care. (September 2019) - Jha, Ajay Kumar; Malik, Vishwas
Anatomical, functional, and pathophysiologic mechanisms of ischemic mitral regurgitation (IMR) are markedly different from the primary mitral regurgitation. The older and ubiquitous cutoff of EROA (effective regurgitant orifice area) and Rvol (regurgitant volume) for IMR has been reinstated in the new guideline after a brief hiatus. There had always been a lack of good-quality evidence for its introduction for guiding IMR severity in the previous guideline, and we still do not have quality evidences that could justify its reintroduction. Unlike primary MR, IMR is usually associated with reduced ejection fraction. Therefore, it appears unrealistic to keep the similar cutoff for primary MR and IMR. The cutoff of severity can be modified according to projected values of Rvol normalized to ejection fraction and EROA normalized to Rvol. In addition, the treatment outcome in these patients is determined by factors (left ventricular dyssynchrony, annular dilatation, tenting area, tenting height, tenting volume, and myocardial viability) other than the simple grading. In this review article, a series of graph have been constructed from the numerical data derived from the literatures on IMR to depict the relationship between EROA, Rvol, left ventricular end diastolic volume, and ejection fraction in order to obtain a reasonable projection formula for EROA and Rvol. Furthermore, a management algorithm has been proposed for patients with IMR undergoing coronary artery bypass grafting based on echocardiographic predictors that influence the postoperative outcome.